Antibody evasiveness of SARS-CoV-2 subvariants KP.3.1.1 and XEC - Wang, Qian; Guo, Yicheng; Mellis, Ian A.; Wu, Madeline; Mohri, Hiroshi; Gherasim, Carmen; Valdez, Riccardo; Purpura, Lawrence J.; Yin, Michael T.; Gordon, Aubree; Ho, David D. (Cell reports (Cambridge), 2025)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to evolve and spread, and it remains critical to understand the functional consequences of mutations in dominant viral variants. The recombinant JN.1 subvariant XEC recently replaced KP.3.1.1 to become the most prevalent subvariant worldwide. Here, we measure the in vitro neutralization of KP.3.1.1 and XEC by human sera, monoclonal antibodies, and the soluble human ACE2 (hACE2) receptor relative to the parental subvariants KP.3 and JN.1. KP.3.1.1 and XEC are slightly more resistant (1.3- to 1.6-fold) than KP.3 to serum neutralization and antigenically similar. Both also demonstrate greater resistance to neutralization by select monoclonal antibodies and soluble hACE2, all of which target the top of the viral spike. Our findings suggest that the upward motion of the receptor-binding domain in the spike may be partially hindered by the N-terminal domain mutations in KP.3.1.1 and XEC, allowing these subvariants to better evade serum antibodies that target the viral spike in the up position and to have a growth advantage. [Display omitted] •KP.3.1.1 and XEC are 1.3- to 1.6-fold more resistant to serum neutralization than KP.3•KP.2 MV booster may elicit higher titers against KP.3.1.1 and XEC than JN.1 infection•Spike mutations F59S and S31Δ are functionally similar for receptor binding and mAb evasion SARS-CoV-2 Omicron JN.1 subvariants KP.3.1.1 and XEC emerged as dominant over parental strains. Wang et al. show that KP.3.1.1 and XEC are similarly antibody evasive due to different spike NTD mutations at interacting amino acids, which likely leads to similar impairments of spike conformational changes.